Improving the performance of photovoltaic cells based on nanocomposites with contorted polycyclic aromatic hydrocarbon additive in bulk heterojunction. Issue 38 (27th September 2021) - Lee, Jaehyeon; Shim, Jaeho; Lee, Joo Song; Choi, Chel-Jong; Yim, Sang-Youp; Jin, Yeonghoon; Yu, Kyoungsik; Park, Young Jae; Ahn, Seokhoon; Son, Dong Ick
Abstract : Cocrystal formation due to a combination between 4Cl-cHBC and bulk heterojunction for improving the efficiency. The power conversion efficiency of a device using the 4Cl-cHBC additives is 9.46%, which is 20.6% higher than that of a reference device. Abstract : Recently, research on the use of additives in photoactive layers to improve the efficiency of solar cells has continued to be conducted. Among them, carbon-based additives serve to increase a device's efficiency by simply and effectively improving the carrier movement. In this work, inverted polymer solar cells (iPSCs) are fabricated based on a blend of PTB7-Th:PC71 BM and PTB7:PC71 BM bulk heterojunction as photoactive materials using mixed additives of 4Cl-carbon-based contorted hexabenzocoronene (4Cl-cHBC). The 4Cl-cHBC additives, a kind of contorted polycyclic aromatic hydrocarbon, added to bulk heterojunction in the iPSC devices, provide a cocrystal modifier and effective charge separation to enhance device performance. The reason for this efficiency improvement is that cocrystal is formed due to a combination between 4Cl-cHBC and the PTB7-Th:PC71 BM bulk heterojunction, which reduces bimolecular recombination in the device and significantly increases short-circuit current and fill factor. The R S and R Sh values of iPSCs based on PTB7-Th:PC71 BM with and without the 4Cl-cHBC additives decreased from 7.0 Ω cm 2 to 4.0 Ω cm 2, and increased from 813 Ω cm 2 to 1226 Ω cm 2, respectively. The calculated average carrier lifetimes at 500 nm for PTB7-Th:PC71 BM and PTB7-Th:PC71 BM with 4Cl-cHBC additives are 4.46 ps and 3.06 ps, respectively. The carrier lifetimes show that the charge separation of PTB7-Th:PC71 BM with 4Cl-cHBC additives is more than 45% faster. As a result, the iPSCs based on the blend of PTB7-Th:PC71 BM and PTB7:PC71 BM with 4Cl-cHBC additives showed maximum power conversion efficiencies of 9.46 and 8.62%, which were 20.6 and 19.95% higher than those of the reference, respectively.